Longitudinal Dynamics of Intact HIV Proviral DNA and Outgrowth Virus Frequencies in a Cohort of Individuals Receiving Antiretroviral Therapy. (20th November 2020) - Falcinelli, Shane D; Kilpatrick, Kayla W; Read, Jenna; Murtagh, Ross; Allard, Brigitte; Ghofrani, Simon; Kirchherr, Jennifer; James, Katherine S; Stuelke, Erin; Baker, Caroline; Kuruc, JoAnn D; Eron, Joseph J; et al.
Abstract: Background: The replication-competent human immunodeficiency virus (HIV) reservoir is the major barrier to cure. The quantitative viral outgrowth assay (QVOA), the gold-standard method to quantify replication-competent HIV, is resource intensive, which limits its application in large clinical trials. The intact proviral DNA assay (IPDA) requires minimal cell input relative to QVOA and quantifies both defective and intact proviral HIV DNA, the latter potentially serving as a surrogate marker for replication-competent provirus. However, there are limited cross-sectional and longitudinal data on the relationship between IPDA and QVOA measurements. Methods: QVOA and IPDA measurements were performed on 156 resting CD4 T-cell (rCD4) samples from 83 antiretroviral therapy-suppressed HIV-positive participants. Longitudinal QVOA and IPDA measurements were performed on rCD4 from 29 of these participants. Results: Frequencies of intact, defective, and total proviruses were positively associated with frequencies of replication-competent HIV. Longitudinally, decreases in intact proviral frequencies were strikingly similar to that of replication-competent virus in most participants. In contrast, defective proviral DNA frequencies appeared relatively stable over time in most individuals. Conclusions: Changes in frequencies of IPDA-derived intact proviral DNA and replication-competent HIV measured by QVOA are similar. IPDA is a promising high-throughput approach to estimate changes in the frequency of the replication-competent reservoir. Abstract : Decay of the HIV reservoir in resting CD4 T cells measured using the intact proviral DNA assay closely resembles that measured using the quantitative viral outgrowth assay.